2014
DOI: 10.1186/1478-4505-12-67
|View full text |Cite
|
Sign up to set email alerts
|

Health systems and policy research evidence in health policy making in Israel: what are researchers’ practices in transferring knowledge to policy makers?

Abstract: BackgroundEnsuring the use of research evidence in health system management and policy decisions is an important challenge in this century. Knowledge transfer and exchange (KTE) has emerged as a paradigm to address the challenges and start closing the ‘know-do’ gap. This area of work is gaining momentum in most developed countries, yet, to date, no work has been performed in Israel within this area. The purpose of this study was to identify which KTE activities health systems and policy researchers in Israel h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 38 publications
3
20
0
Order By: Relevance
“…We were able to identify perceived facilitators among men and women, such as the presence of structures linking researchers and target audiences, the investment of target audiences in KTE efforts and the presence of stable contacts among target audience. To some extent these ndings are in-line with studies conducted in other settings (28)(29)(30).…”
Section: Discussionsupporting
confidence: 89%
“…We were able to identify perceived facilitators among men and women, such as the presence of structures linking researchers and target audiences, the investment of target audiences in KTE efforts and the presence of stable contacts among target audience. To some extent these ndings are in-line with studies conducted in other settings (28)(29)(30).…”
Section: Discussionsupporting
confidence: 89%
“…What is interesting to note is that most of the areas where policymakers identified a need for improvement fall within the responsibilities of the researchers. Most researchers that focus on health systems and policy research in Israel have acknowledged that they are minimally involved in KTE activities [ 34 ]. However, while increasing initiatives both within research production and push efforts to improve the use of HSPR in decision making is important, there are initiatives that can be undertaken by policymakers and decision makers as well.…”
Section: Discussionmentioning
confidence: 99%
“…Most researchers that conduct health systems research in Israel are based either in research institutes, academic institutions, government agencies, the four health insurance funds, or hospital settings, and many researchers have cross appointments in a number of the aforementioned institutions. This previous research has demonstrated that less than half of the respondents were involved in various KTE activities such as interacting with knowledge users throughout the research process and developing reports and summaries that used language appropriate for their target audiences [ 34 ]. More than a third of the researchers in Israel reported that they were frequently or always involved in interactions with target audience through the research process (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The target was health systems and policy researchers from academic institutions, hospital settings, government agencies, the four health insurance funds, and research institutes (for more details on the development of the list of potential respondents, see [30]). All potential respondents were identified by (1) examining publicly available web sites associated with each of the aforementioned institution types and identifying those researchers that focused on health systems and policy, and (2) examining the list of research projects that were funded by the National Institute for Health Policy and obtaining the emails of the associated researchers (email addresses were obtained for all identified respondents).…”
Section: Methodsmentioning
confidence: 99%